KESANTUNAN BERBAHASA DALAM PERCAKAPAN ANTAR DOSEN DI PERGURUAN TINGGI - Sitompul, Siti Jahria; Kesha, Cut Nabilla; Rizki, Julia; Rismawati; Syafrizal (Jurnal Metrum, 2024)
Lecturers as educators at universities should speak according to the norms or maxims of language politeness as a form of providing an example for students in speaking politely. Therefore, this research aims to examine language politeness which is indicated in everyday conversations in the academic sphere, especially conversations between lecturers in universities. This research uses a descriptive qualitative method by collecting data through observation and conversation notes. The data analysis technique consists of three stages, namely data reduction, data presentation and analysis, and drawing conclusions. The results of this research found that there are 5 maxims of language politeness that are carried out in the lecturer's room by lecturers in the Public Administration Study Program in daily conversations. The maxims found consisted of two maxims of generosity, one maxim of appreciation, one maxim of simplicity, one maxim of consensus, and one maxim of sympathy, while the maxim of wisdom was not found during research data collection.